2020
DOI: 10.1038/s41467-019-14184-0
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation upregulates SPINK1 expression and potentiates cellular plasticity in prostate cancer

Abstract: Emergence of an aggressive androgen receptor (AR)-independent neuroendocrine prostate cancer (NEPC) after androgen-deprivation therapy (ADT) is well-known. Nevertheless, the majority of advanced-stage prostate cancer patients, including those with SPINK1-positive subtype, are treated with AR-antagonists. Here, we show AR and its corepressor, REST, function as transcriptional-repressors of SPINK1, and AR-antagonists alleviate this repression leading to SPINK1 upregulation. Increased SOX2 expression during NE-tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 72 publications
4
67
0
Order By: Relevance
“…Additionally, a subset of NEPC patients exhibit elevated levels of SPINK1, suggesting its role in the maintenance of the NE-like phenotype (Tiwari et al, 2020).…”
Section: Cell-intrinsic Factorsmentioning
confidence: 99%
“…Additionally, a subset of NEPC patients exhibit elevated levels of SPINK1, suggesting its role in the maintenance of the NE-like phenotype (Tiwari et al, 2020).…”
Section: Cell-intrinsic Factorsmentioning
confidence: 99%
“…Among the predicted pathways, SPINK1-metallothionein signaling was the top pathway with a significant correlation ( Figure 2C,D). The aberrant activation of SPINK1 signaling could contribute to tumor malignancy, including increased invasion and proliferation of tumor cells [13][14][15]. Both SPINK1 and the metallothionein gene family, including MT1F, MT1G, MT1H, and MT3, were downregulated in the comparison of DDX3X high versus DDX3X low (Figure 2E), suggesting DDX3X's critical role in repressing RCC progression.…”
Section: Knowledge-based Transcriptomic Analysis Revealed That the Spmentioning
confidence: 99%
“…Similar studies had similarly low sample size yet give significance in practice. Tiwari et al showed AR and its transcriptional co-repressor REST modulate SPINK1 expression, and plausible role of SPINK1 in the progression of Neuroendocrine prostate cancer with only few samples (30). Another study by Cheung et al, using only 11 samples per group founded that the Actin alpha cardiac muscle 1 (ACTC1) gene expression would play a role in compensating ADT administration for PCa as a response to ADT-induced muscle loss (31).…”
Section: Adtmentioning
confidence: 99%